Analysis of Policy Strategy for Empowerment of Fisherman in Teluk Village, Labuan Sub-District, Pandeglang Regency - Jumiati, Ipah Ema; Budiati, Ayuning (International Journal of Global Operations Research, 2024)
The community empowerment approach is sought to provide guidance for the sustainability of the livelihoods and lives of the fishing communities of Teluk Village, Labuan District, Pandeglang Regency, especially after being hit by the tsunami (22/12/2018) and the Covid-19 pandemic. Ecosystem preservation also requires commitment from stakeholders. The policy strategy is the government's task that needs to be analyzed, while the community has strong social capital, as a form of survival in facing opportunities, challenges and threats in the management of marine and fishery resources. This study aims to analyze the policy strategy for empowering fishermen in Teluk Village, Labuan District, Pandeglang Regency. The key theory used is the concept of strategy according to Hunger-Wheelen (2003: 9), through observing the external environment to describe opportunities and threats, then observing the internal environment of the organization to describe strengths and weaknesses known as Strengths, Weaknesses (weaknesses). Opportunities (opportunities), and Threats (threats). The approach used in this research is descriptive qualitative. Through this approach it is intended to be able to take a full picture of various phenomena that aim to describe, summarize various conditions, various situations or various social realities of empowering the fishing community in Teluk Village, Labuan District, Pandeglang Regency. The results of the study show that the policy strategy for empowering fishermen in Teluk Village refers to strengthening the internal and external sources of the Pandeglang Regency Maritime Service organization, including efforts in the field of empowering fishermen by carrying out various fisheries business development programs, carrying out fishermen technical guidance for business groups with fishermen. Furthermore, monitoring and evaluation, as well as carrying out reports. The suggestion that the researchers put forward is to increase various efforts to empower fishermen in the Bay Village by encouraging fishermen's involvement in accessing various institutional fishermen empowerment programs and revitalizing various facilities and infrastructure that require development and repair due to the tsunami disaster.